Sustainable palm weevil farming as nutrition supplementation at maternity waiting homes in Liberia - Christopher W. Reynolds; Madison Horton; Jacob Paarechuga Anankware; Joseph Perosky; HaEun Lee; Aloysius Nyanplu; Barsee Zogbaye; Alphonso Kofa; Jody R. Lori (BMC, 2022)
Abstract Background Food insecurity is a global health challenge exacerbated by COVID-19. In Liberia, two-thirds of pregnant women are anemic, one-third of children are stunted, and 70% of households experienced food insecurity due to COVID-19. Edible insects are a nutritious, environmentally responsible, and cost-effective dietary supplement used throughout sub-Saharan Africa. Rearing palm weevil insects at maternity waiting homes (MWHs)-residential dwellings near hospitals where pregnant women await childbirth and receive postpartum services-could serve as a nutritious supplement for expectant mothers in Liberia and provide an income generating activity for MWHs. Methods Following a one-day training, sixteen participants established palm weevil rearing sites at four MWHs in Liberia. Pre- and post-knowledge scores were assessed immediately prior to and following training. Pre-and post-knowledge scores were analyzed using paired t-test. Participants tracked two palm weevil rearing cycles (four months), using harvest amounts, turnover, barriers to implementation, and income generated as metrics. The number of women attending MWHs was recorded throughout the study period (July-December 2020). Results Sixteen participants from four MWHs completed the training and two rearing cycles (four months) successfully. All participants showed statistically significant increases in knowledge scores following the one-day workshop with a pre-test score of 2.31 and post-test score of 7.75 out of 10 (p < 0.001). Over the 6-month study, 217 women stayed in four MWHs. Larval production from the various rearing centers ranged from 120 to 721 larvae, with all four sites producing enough palm weevil to sustain MWH residents who desired to consume the insects. One site successfully commercialized its harvest to sell approximately 50% for a total of 2,000 LD (13 USD) in income. Three of the four sites continued edible insect production beyond the four-month study period. Conclusions An edible insect project using palm weevil larva is one promising intervention as a nutrition supplement for expectant mothers at pre-established MWHs in rural Liberia. Edible insect rearing also has potential as an income generating activity for MWHs. Future studies should focus on addressing common barriers of remote implementation and metric tracking during the COVID-19 pandemic and reinforcing infrastructure to protect larvae rearing supplies.